Molecular Characterization of HOXA2 and HOXA3 Binding Properties - Joshua Mallen; Manisha Kalsan; Peyman Zarrineh; Laure Bridoux; Shandar Ahmad; Nicoletta Bobola (Journal of Developmental Biology, 2021)
The highly conserved HOX homeodomain (HD) transcription factors (TFs) establish the identity of different body parts along the antero–posterior axis of bilaterian animals. Segment diversification and the morphogenesis of different structures is achieved by generating precise patterns of HOX expression along the antero–posterior axis and by the ability of different HOX TFs to instruct unique and specific transcriptional programs. However, HOX binding properties in vitro, characterised by the recognition of similar AT-rich binding sequences, do not account for the ability of different HOX to instruct segment-specific transcriptional programs. To address this problem, we previously compared HOXA2 and HOXA3 binding in vivo. Here, we explore if sequence motif enrichments observed in vivo are explained by binding affinities in vitro. Unexpectedly, we found that the highest enriched motif in HOXA2 peaks was not recognised by HOXA2 in vitro, highlighting the importance of investigating HOX binding in its physiological context. We also report the ability of HOXA2 and HOXA3 to heterodimerise, which may have functional consequences for the HOX patterning function in vivo.